Low-Temperature Atomic Layer Deposited Oxide on Titanium Nitride Electrodes Enables Culture and Physiological Recording of Electrogenic Cells - Dollt, Michele; Reh, Miriam; Metzger, Michael; Heusel, Gerhard; Kriebel, Martin; Bucher, Volker; Zeck, Günther (Frontiers in Neuroscience, 2020)
The performance of electrodes insulated by low-temperature atomic-layer-deposited (ALD) titanium oxide (TiO2) or hafnium oxide (HfO2) for culture of electrogenic cells and for recording of extracellular action potentials is investigated. Insulation of titanium nitride electrodes of microelectrode arrays (MEA) was performed using ALD of nanometer-sized titanium oxide or hafnium oxide at low temperatures (100 - 200°C). The electrode properties, impedance and leakage current were measured and compared. Although electrode insulation using ALD oxides increased the electrode impedance, it did not prevent stable, physiological recordings of electrical activity from electrogenic cells (cardiomyocytes and neurons). The insulation quality, estimated from leakage current measurements, was below 100 nA/cm2 in a range of 3 Volts. Cardiomyocytes were successfully cultured and recorded after five days on the insulated MEAs with signal shapes similar to the recordings obtained using uncoated electrodes. Light-induced electrical activity of retinal ganglion cells was recorded using a CMOS-based MEA insulated with HfO2 without driving the recording electrode into saturation. The presented results demonstrate that low-temperature ALD-deposited titanium oxide and hafnium oxide are biocompatible, biostable and enable physiological recordings. Our results indicate that nanometer-sized ALD insulation may be used to protect electrodes for long-term biological applications.